Zakat dan Distribusi Harta - Samsul Basri (TASAMUH: Jurnal Studi Islam, 2019)
The focus of this discussion is on Zakat and Property Distribution. The purpose of this study is to provide an explanation of how the Sharia views on zakat and to find out how the benefits of the distribution of assets. This study examines research that reveals the wisdom behind zakat and property distribution in improving people's welfare. The results of the discussion cite that zakat is one of the requirements for Muslims. While the benefits of its distribution provide a positive impact in terms of improving people's lives.